Le coming out des enseignants homosexuels. Intérêt et limites de l’approche goffmanienne - Stéphane Biron; Jean Nizet (Recherches Sociologiques et Anthropologiques, 2017)
The authors are interested in the coming out of gay teachers. Basing themselves on Stigmate (Goffman, 1975), they compare the author’s theory with interviews carried out with six teachers in French-speaking Belgian catholic teaching. Nuancing a dichotomic vision of coming out (staying in the closet or getting out of it), the authors show how the Goffmanian theory allows us to account for the variety of strategies of gay teachers in interacting with their professional entourage (students, colleagues, administration). However, the research results also accentuate the limits of Goffman’s theory. The microsociological level is not capable of validly grasping the complexity of the interactions of gay teachers. Indeed, the situation of interaction is influenced by macrosocial phenomena and the biographical trajectory of the people interviewed.